Pemanfaatan Media Pembelajaran : Buku Cerita Bergambar Berbasis Mitigasi Bencana Untuk Meningkatkan Literasi Informasi - Yoesrina Novia Vini Syafitri; Dewi Fitriani; Rahmatika Layyinah; Nurani Hadnistia Darmawan; Hilman Hilmawan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Information literacy is an essential skill for elementary school students, particularly in understanding disaster mitigation materials. Engaging learning media can help enhance this ability. The purpose of this study was to determine the effect of using disaster mitigation-based picture storybook media on the information literacy of elementary school students. This research employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of fourth-grade students at Cimangkok Elementary School, with tests as the research instrument. Data were analyzed using descriptive statistics and a t-test. The average pretest score of the experimental class was 45.6, while the control class scored 44. The average posttest score of the experimental class increased to 75, compared to 53 in the control class. The hypothesis test showed a significance value of 0.001 < a = 0.05, indicating that Ho was rejected and Ha was accepted. Based on these results, the use of disaster mitigation-based picture storybook media has a significant effect on improving elementary school students’ information literacy.